أهمية الحـوار في بناء السلام والتعايش السلمي - Fouad Larhzizer (Pascasarjana Universitas Wahid hasyim Semarang, 2021)
ملخص: إن موضوع الحوار من المواضيع التي حظيت باهتمام العديد من المفكرين والسياسيين والباحثين في الوقت الراهن، نظرا لأهميته في التقريب بين وجهات النظر المتباينة، وتحقيق التعايش السلمي والعيش المشترك على أُسُس من الاحترام المتبادل والحرص على المصالح المشتركة. وتتجلى أهمية الحوار في علاج العديد من المشاكل الاجتماعية والاقتصادية والسياسية، فهو ضرورة واقعية تُمليها ظُروف العصر في العديد من المناطق التي تَشْهد صِراعات مُستمرة، فهو السبيل الوحيد لتحقيق السلم والأمن الاجتماعي. وقد قسمت هذه الدراسة إلى أربعة محاور، خصصت المحور الأول لمفهوم الحوار، بينما أفردت الثاني للحديث عن مفهوم السلم، في حين تناولت في الثالث مفهوم التعايش، وفي الرابع أهمية الحوار في بناء السلام والتعايش، ثم ختمتها بخلاصة للموضوع. الكلمات المفاتيح: الحوار، السلم، التعايش السلمي. Abstract The topic of dialogue is one of the topics that has attracted the attention of many thinkers, politicians and researchers at the present time, due to its importance in bridging the divergent viewpoints, and achieving peaceful coexistence on foundations of mutual respect and concern for common interests. The importance of dialogue is reflected in the treatment of many social, economic and political problems, as it is a realistic necessity dictated by the circumstances of the times in many areas experiencing continuous conflicts, as it is the only way to achieve peace and social security. This study was divided into four axes, the first axis was devoted to the concept of dialogue, the second was devoted to the concept of peace, while the third it dealt with the concept of coexistence, and the fourth the importance of dialogue in building peace and coexistence, then concluded with a summary of the topic. Key words: dialogue, peace, peaceful coexistence.